Customer experience innovation : how to get a lasting market edge - Dew, Robert; Allen, Cyrus (Emerald Publishing Limited, 2018)
Companies who invest in successful Customer eXperience (CX) innovation stand out from the crowd. Markets tend to reward these companies because it is rare for firms to try something new, much less prove customer acceptance of their attempted innovations. Firms offering remarkable CX create loyal customers who happily pay more for their products and services, and then refer them to other customers for free. This book outlines innovative processes used to research, conceive and develop innovations in the CX space for both large and small companies. The challenge is not so much finding out what customers like, as it is remaining apart from the crowd of rivals and copycats. Written as a practical guide for managers with a background in line management, operations, marketing, finance or customer service, this book contains a simple framework with an extensive range of design thinking and creative problem solving tools. Starting with a validation for investing in improving your firms CX, the book also provides a primer on competitive advantage, the most critical objective of strategic planning. Mastering the books content creates the potential for any business manager or owner to find a hard-to-copy market advantage and drive their business growth.
Includes index.
Keywords: Consumer satisfaction.; Customer relations.; Business & Economics / Customer Relations.; Sales & marketing.; elektronické knihy; electronic books